1989
DOI: 10.1111/j.1365-3024.1989.tb00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross–reactivity of antibody against an epitope of the Plasmodium falciparum second merozoite surface antigen

Abstract: Monoclonal antibodies directed against the 51 kD merozoite surface antigen of Plasmodium falciparum also bind to other antigens within the infected cell. The sizes of these cross-reacting antigens have been characterized. Immunofluorescence due to the reaction of one of the monoclonal antibodies with these cross-reacting antigens was localized in the intra-erythrocytic parasite and in granules in the infected red cell cytoplasm. This immunofluorescence could be distinguished from the merozoite surface antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…8G10, which is reactive with the FC27 central variable region, labeled newly invaded rings to a higher degree than other antibodies, but this labeling was still minimal compared to the labeling of merozoites prior to, during, or immediately after invasion. This may indicate that the epitopes recognized by this antibody are more accessible or degraded more slowly than other epitopes, or the labeling seen may reflect the cross-reactivity of this MAb, which was reported previously (71).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…8G10, which is reactive with the FC27 central variable region, labeled newly invaded rings to a higher degree than other antibodies, but this labeling was still minimal compared to the labeling of merozoites prior to, during, or immediately after invasion. This may indicate that the epitopes recognized by this antibody are more accessible or degraded more slowly than other epitopes, or the labeling seen may reflect the cross-reactivity of this MAb, which was reported previously (71).…”
Section: Resultssupporting
confidence: 71%
“…The specificity of the MAbs to MSP2 was previously confirmed via Western blotting; all MAbs were specific to MSP2, with no cross-reactivity to other parasite proteins, except for MAb 9G8, which has some cross-reactivity to spectrin (60). 8G10 was reported previously in other studies to be cross-reactive to some extent with other parasite proteins, which have not been identified (71). As we lacked a MAb against the N-terminal region of MSP2 that reacted with the native surfacelocated antigen by IF microscopy, N-terminally specific antibodies were purified from rabbit polyclonal serum that had been generated by vaccination with full-length 3D7 MSP2.…”
Section: Resultssupporting
confidence: 62%
“…Immune selection would be consistent with the diversity seen in AMA1, 44 and inefficient antibody responses are elicited to the repeat regions of the other antigens studied. 45,46 Therefore, the significant change in isolate genotype between the first and the fourth time points of this study is notable. We have shown that the dominant strain from the first time point is initially involved in infections throughout the study region.…”
Section: Discussionmentioning
confidence: 77%
“…Early studies showed that mouse monoclonal antibodies (MAbs) that discriminated between heterologous parasites affected homologous in vitro growth inhibition (7,13). Curiously, there is scant evidence of the inability of allele-specific MAbs to inhibit heterologous parasites in vitro (45).…”
mentioning
confidence: 99%